2018
DOI: 10.1186/s40814-018-0345-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a smartwatch-based intervention providing feedback of daily activity within a research-naive stroke ward: a pilot randomised controlled trial

Abstract: BackgroundThe majority of stroke patients are inactive outside formal therapy sessions. Tailored activity feedback via a smartwatch has the potential to increase inpatient activity. The aim of the study was to identify the challenges and support needed by ward staff and researchers and to examine the feasibility of conducting a randomised controlled trial (RCT) using smartwatch activity monitors in research-naive rehabilitation wards. Objectives (Phase 1 and 2) were to report any challenges and support needed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…This study has some limitations. First, the sample size is rather small and leads to reduced power of the study, but comparable with phase II studies in the field (47)(48)(49)(50). Results should be interpreted with caution due to the large confidence intervals but the higher between-group motor improvement for motor therapy could be considered substantial and clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…This study has some limitations. First, the sample size is rather small and leads to reduced power of the study, but comparable with phase II studies in the field (47)(48)(49)(50). Results should be interpreted with caution due to the large confidence intervals but the higher between-group motor improvement for motor therapy could be considered substantial and clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Consumer-based activity trackers are increasingly being evaluated for use in research. Recent examples includes Lawrie et al [5] and Beukenhorst et al [6], who included smart watches in their research protocols. The major limitation of these devices is the limited knowledge of device validity.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies took place in North America (41/103, 40%) [ 46 - 49 , 52 , 55 , 56 , 60 , 64 - 67 , 69 , 70 , 72 , 74 , 76 - 78 , 80 , 85 - 88 , 92 , 93 , 97 , 99 , 101 , 108 - 110 , 126 - 129 , 137 , 138 , 141 , 142 , 145 ] and Europe (35/103, 34%) [ 51 , 53 , 54 , 57 , 58 , 62 , 63 , 68 , 71 , 79 , 81 - 84 , 89 , 111 , 113 - 125 , 132 , 136 , 140 , 143 , 146 , 147 ], with the remainder in Asia (16/103, 16%) [ 50 , 59 , 61 , 91 , 94 , 95 , 98 , 100 , 102 - 104 , 107 , 135 , 139 ,…”
Section: Resultsmentioning
confidence: 99%
“…Over three-quarters (83/103, 81%; 2508 participants) of studies reported the time since the onset of stroke. Of these 83 studies, 1 (1%; 48 participants) study [ 91 ] was conducted in the acute phase, 14 (17%; 504 participants) studies [ 60 , 61 , 68 , 74 , 79 , 92 , 100 , 102 , 109 , 114 , 133 , 144 , 146 , 148 ] were conducted in the early subacute phase, 11 (13%; 316 participants) studies [ 59 , 65 , 66 , 72 , 75 , 76 , 81 , 104 , 107 , 121 , 134 ] were conducted in the late subacute phase, and 57 (69%; 1640 participants) studies [ 46 , 48 , 49 , 51 , 53 , 54 , 57 , 63 , 64 , 67 , 69 , 70 , 73 , 78 , 80 , 82 , 84 , 85 , 88 , 89 , 93 - 99 , 101 , 103 , 105 , 106 , 108 , 111 - 113 , 117 - 120 , 122 - 125 , 127 - 131 , 13...…”
Section: Resultsmentioning
confidence: 99%